Catalytic Antioxidant Aeol 10150 Treatment Ameliorates Sulfur Mustard Analog 2-Chloroethyl Ethyl Sulfide Associated Cutaneous Toxic Effects - Tewari-Singh, Neera (2014)
Our previous studies and other published reports with the chemical warfare agent sulfur mustard (SM) and its analog 2-chloroethyl ethyl sulfide (CEES) have indicated a role of oxidative stress in skin injuries caused by these vesicating agents. We examined the effects of the catalytic antioxidant AEOL 10150 in attenuation of CEES-induced toxicity in our established skin injury models (skin epidermal cells and SKH-1 hairless mice) to validate the role of oxidative stress in the pathophysiology of mustard vesicating agents. Treatment of mouse epidermal JB6 and human HaCaT cells with AEOL 10150 (50 μM) 1 h post CEES exposure resulted in significant (p<0.05) reversal of CEES-induced decreases in both cell viability and DNA synthesis. Similarly, AEOL 10150 treatment 1 h after CEES exposure attenuated CEES-induced DNA damage in these cells. Similar AEOL 10150 treatments also caused significant (p<0.05) reversal of CEES-induced decreases in cell viability in normal human epidermal keratinocytes. Cytoplasmic and mitochondrial reactive oxygen species measurements showed that AEOL 10150 treatment drastically ameliorated the CEES-induced oxidative stress in both JB6 and HaCaT cells. Based on AEOL 10150 pharmacokinetic studies in SKH-1 mouse skin, mice were treated with topical formulation plus subcutaneous (injection; 5 mg/kg) AEOL 10150, 1 h after CEES (4 mg/mouse) exposure and every 4 h thereafter for 12 h. This AEOL 10150 treatment regimen resulted in over 50% (p<0.05) reversal in CEES-induced skin bi-fold and epidermal thickness, myeloperoxidase activity, and DNA oxidation in mouse skin. Results from this study demonstrate potential therapeutic efficacy of AEOL 10150 against CEES-mediated cutaneous lesions supporting AEOL 10150 as a medical countermeasure against SM-induced skin injuries.